Roles of Polymorphonuclear Neutrophils in Ischemic Brain Injury and Post-Ischemic Brain Remodeling - Mohamud Yusuf, Ayan; Hagemann, Nina; Ludewig, Peter; Gunzer, Matthias; Hermann, Dirk M. (Frontiers in Immunology, 2022)
Following ischemic stroke, polymorphonuclear neutrophils (PMNs) are rapidly recruited to the ischemic brain tissue and exacerbate stroke injury by release of reactive oxygen species (ROS), proteases and pro-inflammatory cytokines. PMNs may aggravate post-ischemic microvascular injury by obstruction of brain capillaries, contributing to reperfusion deficits in the stroke recovery phase. Thus, experimental studies which specifically depleted PMNs by delivery of anti-Ly6G antibodies or inhibited PMN brain entry, e.g., by CXC chemokine receptor 2 (CXCR2) or very late antigen-4 (VLA-4) blockade in the acute stroke phase consistently reduced neurological deficits and infarct volume. Although elevated PMN responses in peripheral blood are similarly predictive for large infarcts and poor stroke outcome in human stroke patients, randomized controlled clinical studies targeting PMN brain infiltration did not improve stroke outcome or even worsened outcome due to serious complications. More recent studies showed that PMNs have decisive roles in post-ischemic angiogenesis and brain remodeling, most likely by promoting extracellular matrix degradation, thereby amplifying recovery processes in the ischemic brain. In this minireview, recent findings regarding the roles of PMNs in ischemic brain injury and post-ischemic brain remodeling are summarized.